Late cortical positivity and cardiac responsitivity in female dental phobics when exposed to phobia-relevant pictures - Leutgeb, Verena (Elsevier, 2011)
OBJECTIVES: Dental phobia is currently classified as a specific phobia of the blood-injection-injury (BII) subtype. In another subtype, animal phobia, enhanced amplitudes of late event-related potentials have consistently been identified for patients during passive viewing of disorder-relevant pictures. However, this has not been shown for BII phobics, and studies with dental phobics are lacking. Findings on cardiac responses in BII phobia during exposure are heterogeneous, as some studies showed a diphasic pattern of heart rate acceleration and deceleration, whereas others observed pure acceleration. In contrast, heart rate increase has consistently been shown for dental phobics, resembling the reaction of animal phobics. Moreover, the BII subtype is characterized by elevated disgust reactivity whereas the role of habitual disgust proneness in dental phobia is unclear. METHODS: We recorded the electroencephalogram and the electrocardiogram from 18 dental phobic and 18 healthy women while they watched pictures depicting dental treatment, disgust, fear and neutral items. RESULTS: Phobics relative to controls showed an enhanced late positive potential (300–700 ms) and heart rate acceleration towards phobic material, reflecting motivated attention and fear. Affective ratings revealed that dental phobics experienced significantly higher levels of fear than disgust during exposure to phobia-relevant material. Patients' elevated habitual disgust proneness was restricted to specific domains, such as the oral incorporation of offensive objects. CONCLUSION: The psychophysiology of dental phobia resembles the fear-dominated subtypes of specific phobia reported in earlier studies. Future studies should continue to investigate whether the current classification of this disorder as BII phobia needs to be reconsidered.